Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:
\(VT=\sqrt{3x^2-6x+19}+\sqrt{x^2-2x+26}\)
\(=\sqrt{3\left(x-1\right)^2+16}+\sqrt{\left(x-1\right)^2+25}\ge4+5=9\)
\(VP=8-x^2+2x=9-\left(x-1\right)^2\le9\)
Dấu = xảy ra khi \(x=1\)
\(\sqrt{14-8\sqrt{3}}\)\(=\sqrt{6-2.4.\sqrt{3}+8}\)
\(=\sqrt{\left(\sqrt{6}\right)^2-2\sqrt{3.16}+\left(\sqrt{8}\right)^2}\)
\(=\sqrt{\left(\sqrt{6}\right)^2-2\sqrt{48}+\left(\sqrt{8}\right)^2}\)
\(=\sqrt{\left(\sqrt{6}-\sqrt{8}\right)^2}\)
\(=\sqrt{6}-\sqrt{8}\)
11x^2-490x-3000=0
<=> 11x^2+60x-550x-3000=0
<=> 11x(x-50)-60(x-50)=0
<=> (x-50)(11x-60)=0
<=> x=50 hoặc x=60/11
Đặt a=1000^2012 thì \(A=\frac{a+2}{a-1}\) ; \(B=\frac{a}{a-3}\)
Xét \(A-B=\frac{a+2}{a-1}-\frac{a}{a-3}=\frac{\left(a+2\right)\left(a-3\right)-a\left(a-1\right)}{\left(a-1\right)\left(a-3\right)}\)
\(=\frac{a^2-a-6-a^2+a}{\left(a-1\right)\left(a-3\right)}=\frac{-6}{\left(a-1\right)\left(a-3\right)}\)
Do \(a>1;a>3\) nên \(\left(a-1\right)\left(a-3\right)>0\Leftrightarrow A-B< 0\)
Do đó \(A>B\)